No ordinary Christmas - Calhoune, Belle (Calhoune, Belle. Mistletoe, Maine novels, 2021)
Mistletoe, Maine, is buzzing and not just because Christmas is around the corner! Dante West, local cutie-turned-Hollywood hunk, is returning home to make his next movie. Everyone in town is excited...except librarian Lucy Marshall. When Dante took off for LA without warning--or even a goodbye--he broke Lucy's heart. She swore not to spend one more minute thinking about her ex, but Dante makes an offer Lucy's struggling library can't refuse: a major donation to film on-site. Dante is thrilled to help boost his hometown's economy and finally begin making amends to the people he hurt years ago when he left, starting with Lucy. But seeing his former best friend on set every day feels a lot less like closure and more like a fresh start. It's one thing for Dante to fall for Lucy all over again, quite another for a famous movie star and a small-town librarian to find lasting romance. Can the magic of the holiday season give Lucy and Dante's first love a second chance?